(untitled) (Phillippines, 2017)
This is repost introduce about households' perception of arsenic-contaminated water and determinants of piped water connection in arsenic-contaminated areas in the red river delta, Vietnam.
Keywords: Arsenic,Arsenic; Khía canh môi trường,Environmental aspects